Evaluation of the Freezability of the Bovine Epididymis Tail Sperm with the Addition of Antioxidants - Passamani da Cruz, G.; Zanfrilli Dos Santos, A. P.; de Freitas Guaitolini, C. R.; Tramontin, M. L.D.; Rigoto, R. P.; Crespilho, A. M.; Dell'Aqua, C. P.F. [UNESP]; Martins, M. I.M.; Marques, A. B.; Hidalgo, M. M.T.; Sestari, D. A.O.; Magalhaes, R.; et al. (My University, 2021)
BACKGROUND: The cryopreservation and recovery of epididymis tail sperm is an important biotechnology dependent on the composition of the freezing medium. OBJETIVE: To evaluate the effect of melatonin, added to commercial freezing medium extender, on the kinetics and viability of bovine epididymis tail sperm. MATERIAL AND METHODS: Five routines were performed, each consisting of eight epididymis and the structures were sliced onto a glass plate containing a commercial diluting medium for Botubov. The samples were divided into four groups, with 80 x 106 spermatozoa per mL. Group 1: samples diluted in Botubov. Group 2: samples centrifuged (600 g, 10 min), and the pellet re-suspended in Botubov. Group 3, samples diluted in Botubov containing 100 pM melatonin. Group 4: samples centrifuged (600 g, 10 min) and the pellet resuspended in Botubov with 100 pM melatonin. The samples were transferred to 0.5 mL straws at 40 x 106 viable spermatozoa, stabilized at 5º C for 4 h, transferred to liquid nitrogen vapour for 20 min, dipped in liquid nitrogen and stored in a cryogenic cylinder. After thawing (46ºC, 15s), sperm kinetics and viability parameters were evaluated. RESULTS: There was no difference in the parameters of total motility (MT, %), progressive motility (MP, %), progressive linear velocity (VSL, µm/s), curvilinear velocity (VCL, µm/s), linearity (LIN, %), spermatozoa with rapid movement (RAP, %) and level of intact plasma membranes and acrosome (IPMA, %) among the groups studied. However, a difference was observed between the routines performed. CONCLUSION: The protocol for freezing bovine epididymis tail sperm is applicable; however, there is an influence of the epididymis used, for the best efficacy of this biotechnology.